Chemical Composition, Antiviral against avian Influenza (H5N1) Virus and Antimicrobial activities of the Essential Oils of the Leaves and Fruits of Fortunella margarita, Lour. Swingle, Growing in Egypt - Nabaweya A. Ibrahim, Seham S. El-Hawary, Magdy M. D. Mohammed, Mohamed A. Farid, Nayera A. M. AbdelWahed, Mohamed A. Ali, Eman A. W. El-Abd (Journal of Applied Pharmaceutical Science, 2015)
Essential oils of the fresh leaves and fruits of Fortunella margarita Lour. Swingle (Family: Rutaceae) were prepared by hydrodistillation method, which resulted with 0.27 and 0.30% respectively. The resulted oils of both organs were analyzed by GC/MS which revealed the presence of twenty compounds in the leaves oil representing 86.96% of the oil, from which gurjunene, eudesmol and muurolene were identified as major compounds. The fruit’s oil was found to contain fourteen compounds representing 77.77% of the oil, of which terpineol, t-carveol, limonene, muurolene and cadinene represented the major compounds. The antiviral activity of the essential oils of both leaves and fruits was tested against avian influenza-A virus (H5N1), and the results revealed higher potency of fruits oil. Moreover, the essential oils of the leaves and fruits were investigated for their antimicrobial and antifungal activities. The oil of the leaves showed antimicrobial activity higher than that of the fruits at dilution (1:50 v/v) against Bacillus subtilis, Staphylococcus aureus, Sarcina luta and Streptococcus faecalis, also it has a moderate activity against Escherichia coli, Klebsilla pneumonia and Pseudomonas aeroginosa. On the other hand, the antifungal activity of the leaves and fruits revealed that the fruits exhibited higher activity than that of the leaves against Aspergillus niger and Candida albicans.
Keywords: Fortunella margarita Lour. Swingle, Rutaceae, essential oil, antiviral, antimicrobial.